(untitled) (Baghdad Science Journal, 2025)
Eighteen new cyclic imides (maleimides) conncted to benzothiazole moiety through sulfonamide group were synthesized via multistep synthesis.The first step involved preparation of two maleamic acids N-phenylmaleamic acid and N-benzylmaleamic acid via reaction of maleic anhydride with aniline or benzyl amine.Dehydration of the prepared amic acids by treatment with acetic anhydride and anhydrous sodium acetate in the second step afforded N-phenylmaleimide and N- benzyl maleimide which in turn were treated with chlorosulfonic acid in the third step to afford 4-(N-maleimidyl) phenyl sulfonyl chloride and 4-(N-maleimidyl) benzyl sulfonyl chloride respectively.In the Fourth step of this work each one of the two prepared maleimidyl sulfonyl chlorides was introduced in reaction with nine substituted-2-amino benzothiazole compounds producing nine N-(4-(N-substituted benzothiazole -2-yl) sulfonamido phenyl) maleimides and nine N-(4-(N-substituted benzothiazole-2-yl)snlfonamido benzyl) maleimides.More over another new six sulfonamide phenyl and benzyl maleimides substituted with other heterocycles (pyridine and phenazone )were prepared via reaction of 4-(N-maleimidyl) phenyl and benzyl sulfonyl chlorides with heterocyclic amines including (2-amino pyridine,4-amino-pyridine,4-aminophenazone). Microbiological activity of the prepared compounds against two typs of bacteria(staphylococcus aureus and klebsiella pneumonia) and (candida albicans) fungi were evaluated and the results showed that these compounds have good antibacterial and good antifungal activities.